The Effect of Variations in Coil Types and Ignition Degree Mapping Using A Programmable CDI on Power in A 110 CC Gasoline Motorcycle - Aprilian Rizki; sugeng hadi susilo (PT. ELSHAD TECHNOLOGY INDONESIA, 2025)
In the automotive world, power reduction in long-used motorcycles is a common issue that can affect vehicle performance. Over time, engine components experience wear and decreased efficiency, leading to reduced power output. One solution to address this problem is optimizing ignition settings by upgrading the CDI (Capacitor Discharge Ignition) and replacing the standard coil with an aftermarket coil. Upgrading the CDI and replacing the standard coil with an aftermarket one aim to improve engine power, as the standard CDI has a relatively low output and the standard coil has a limited output capacity. Therefore, the coil must match the output capacity of the upgraded CDI. This study aims to enhance the performance of a 110cc four-stroke engine. The study method used is a quantitative experimental approach, and data processing is carried out using two-way ANOVA analysis of the test results, processed in Microsoft Excel, with the average results taken from three trials per variation. The independent variables in this study are the racing coil with a voltage greater than the standard (up to 90 kV) and ignition timing mapping with a programmable CDI, while the dependent variable is power. The results of the study show that the ignition timing set at 13 degrees and the use of the BRT coil provided the highest power output, reaching 8.33 horsepower at 8000 rpm. This outcome is due to the critical role of ignition timing in controlling fuel combustion in the combustion chamber, where an earlier explosion with a larger spark results in higher power output